2019
DOI: 10.3390/ijerph16101717
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consumption Patterns on the Generation of Municipal Solid Waste in China: Evidences from Provincial Data

Abstract: Municipal solid waste (MSW) is the derivative of urban development and it is harmful to the environment and residents’ health. But with sustainable MSW management, MSW can be applied as an important renewable energy. In order to achieve sustainable MSW management, it is necessary to understand the mechanism of MSW generation. Consumption patterns differ in various regions of China, which make the influencing factors of MSW have unique characteristics. To explore the factors influencing MSW generation in China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 41 publications
3
42
0
1
Order By: Relevance
“…However, land ll is likely to bring about greenhouse gases emissions, generation of large amount of leachate, and nally environmental pollutions (Ma and Liu 2019). Although incineration could reduce the volume of food waste, it needs a high demand for energy, and the process itself is prone to produce harmful and or greenhouse gases (Liu et al 2019).…”
Section: Components Of Urban and Rural Degradable Household Garbagementioning
confidence: 99%
“…However, land ll is likely to bring about greenhouse gases emissions, generation of large amount of leachate, and nally environmental pollutions (Ma and Liu 2019). Although incineration could reduce the volume of food waste, it needs a high demand for energy, and the process itself is prone to produce harmful and or greenhouse gases (Liu et al 2019).…”
Section: Components Of Urban and Rural Degradable Household Garbagementioning
confidence: 99%
“…In Taiwan, six special municipalities and 16 cities and counties cover a large variety of urbanization and settlement characteristics, such as the population areal density and electricity and water consumption, both within the administration boundary and per capita. There are many socio-economic, environmental, and MSW service factors employed to correlate or evaluate MSW systems [15], such as households [16], GDP per capita [17], and recycling rates [18]. Since all human activities require electricity and water consumption, the present study aims to compare the correlation between MSW, population, and utility consumption to identify the most pertinent factors influencing MSW generation.…”
Section: Objectivesmentioning
confidence: 99%
“…Some authors analyzed the impact of consumption factors on the generation of municipal solid waste (Liu et al (2019); Lu et al (2017); Mahees et al 2011;Hage et al 2018). The results showed that developing regions generate more waste than developed regions.…”
Section: Literature Reviewmentioning
confidence: 99%